Shewanella sp. T2.3D-1.1 a Novel Microorganism Sustaining the Iron Cycle in the Deep Subsurface of the Iberian Pyrite Belt - Guillermo Mateos; Adrián Martínez Bonilla; Sofía de Francisco de Polanco; José M. Martínez; Cristina Escudero; Nuria Rodríguez; Irene Sánchez-Andrea; Ricardo Amils (Microorganisms, 2022)
The Iberian Pyrite Belt (IPB) is one of the largest deposits of sulphidic minerals on Earth. Río Tinto raises from its core, presenting low a pH and high metal concentration. Several drilling cores were extracted from the IPB’s subsurface, and strain T2.3D-1.1 was isolated from a core at 121.8 m depth. We aimed to characterize this subterranean microorganism, revealing its phylogenomic affiliation (Average Nucleotide Identity, digital DNA-DNA Hybridization) and inferring its physiology through genome annotation, backed with physiological experiments to explore its relationship with the Fe biogeochemical cycle. Results determined that the isolate belongs to the Shewanella putrefaciens (with ANI 99.25 with S. putrefaciens CN-32). Its genome harbours the necessary genes, including omcA mtrCAB, to perform the Extracellular Electron Transfer (EET) and reduce acceptors such as Fe3+, napAB to reduce NO3− to NO2−, hydAB to produce H2 and genes sirA, phsABC and ttrABC to reduce SO32−, S2O32− and S4O62−, respectively. A full CRISPR-Cas 1F type system was found as well. S. putrefaciens T2.3D-1.1 can reduce Fe3+ and promote the oxidation of Fe2+ in the presence of NO3− under anaerobic conditions. Production of H2 has been observed under anaerobic conditions with lactate or pyruvate as the electron donor and fumarate as the electron acceptor. Besides Fe3+ and NO3−, the isolate also grows with Dimethyl Sulfoxide and Trimethyl N-oxide, S4O62− and S2O32− as electron acceptors. It tolerates different concentrations of heavy metals such as 7.5 mM of Pb, 5 mM of Cr and Cu and 1 mM of Cd, Co, Ni and Zn. This array of traits suggests that S. putrefaciens T2.3D-1.1 could have an important role within the Iberian Pyrite Belt subsurface participating in the iron cycle, through the dissolution of iron minerals and therefore contributing to generate the extreme conditions detected in the Río Tinto basin.